Zebra fish myc family and max genes: differential expression and oncogenic activity throughout vertebrate evolution. - Schreiber-Agus, N (1993)
To gain insight into the role of Myc family oncoproteins and their associated protein Max in vertebrate growth and development, we sought to identify homologs in the zebra fish (Brachydanio rerio). A combination of a polymerase chain reaction-based cloning strategy and low-stringency hybridization screening allowed for the isolation of zebra fish c-, N-, and L-myc and max genes; subsequent structural characterization showed a high degree of conservation in regions that encode motifs of known functional significance. On the functional level, zebra fish Max, like its mammalian counterpart, served to suppress the transformation activity of mouse c-Myc in rat embryo fibroblasts. In addition, the zebra fish c-myc gene proved capable of cooperating with an activated H-ras to effect the malignant transformation of mammalian cells, albeit with diminished potency compared with mouse c-myc. With respect to their roles in normal developing tissues, the differential temporal and spatial patterns of steady-state mRNA expression observed for each zebra fish myc family member suggest unique functions for L-myc in early embryogenesis, for N-myc in establishment and growth of early organ systems, and for c-myc in increasingly differentiated tissues. Furthermore, significant alterations in the steady-state expression of zebra fish myc family genes concomitant with relatively constant max expression support the emerging model of regulation of Myc function in cellular growth and differentiation.